Deposition, Characterization, and Modeling of Scandium-Doped Aluminum Nitride Thin Film for Piezoelectric Devices - Qiaozhen Zhang (MDPI AG, 2021)
In this work, we systematically studied the deposition, characterization, and crystal structure modeling of ScAlN thin film. Measurements of the piezoelectric device’s relevant material properties, such as crystal structure, crystallographic orientation, and piezoelectric response, were performed to characterize the Sc0.29Al0.71N thin film grown using pulsed DC magnetron sputtering. Crystal structure modeling of the ScAlN thin film is proposed and validated, and the structure–property relations are discussed. The investigation results indicated that the sputtered thin film using seed layer technique had a good crystalline quality and a clear grain boundary. In addition, the effective piezoelectric coefficient d33 was up to 12.6 pC/N, and there was no wurtzite-to-rocksalt phase transition under high pressure. These good features demonstrated that the sputtered ScAlN is promising for application in high-coupling piezoelectric devices with high-pressure stability.